An Uncommon Complication With Use of Topical Local Anesthetic Agents: Methemoglobinemia. (November 2016) - Panikkath, Ragesh; Panikkath, Deepa; Wischmeyer, Jason
Abstract : Although the use of topical local anesthetics is generally safe, several potentially fatal complications have been reported. Methemoglobinemia is a rare but potentially fatal complication. Methemoglobin is a naturally occurring oxidized metabolite of hemoglobin, and physiologic levels (<1%) are normal. Methemoglobinemia can be congenital or acquired. Several drugs including topical anesthetic agents like benzocaine can induce this condition. Sudden appearance of cyanosis, with a disproportionately better oxygen saturation of 85% after use of local anesthetics can be a helpful for diagnosis.